The Function of Sharia Banks in Optimizing Waqf as the Integration of the Commercial Economy and Social Economy to Improve Public Welfare - Imaniyati, Neni Sri; Firmansyah, Arif; Alamsyah, Indra Fajar; Kamilah, Anita (KnE Social Sciences, 2024)
The pillars of Islamic Economics and Finance cover commercial finance and social finance, such as zakat and waqf. Based on data from BAZNAS in 2020, ziswaf (zakat, infaq, alms, and waqf ) funds among Muslims in Indonesia were Rp12.5 trillion, while its potential reached Rp327.6 trillion. The potential for cash waqf is Rp80 trillion every year. Meanwhile, based on data from the Ministry of Religion in 2018, the realization of cash waqf recorded from 2011 to 2018 was an average Rp31.9 billion each year. This means that cash waqf still has enormous potential to be developed. Therefore, the study was conducted to (1) explain the regulation of bank functions to achieve the goal of increasing people’s welfare and (2) find alternative efforts to improve bank functions in improving people’s welfare through the integration of the commercial and social economy. The method used was normative juridical approach with descriptive and prescriptive analysis, while the type of data used was secondary data obtained through a literature review. This research provided an in-depth study of the function of Islamic banks in optimizing the potential of waqf through the integration of the commercial economy and social economy in an effort to improve community welfare. The data were then analyzed using qualitative juridical analysis through legal interpretation. The results showed that (1) based on Law Number 21 Year 2008, the function of Sharia banks is as a financial intermediary, which collects funds from the public in the form of deposits, namely savings, time deposits, and demand deposits. Sharia banks cannot accept deposits in the form of cash waqf. (2) As an effort to integrate the commercial and social economy to improve people’s welfare, it is better to amend the Sharia Banking Law that allows Sharia banks to accept deposits in the form of cash waqf, so that the proceeds can be channeled into productive activities. Keywords: commercial economy, Sharia Bank, social economy, Waqf